Dabigatran use in elderly patients with atrial fibrillation - Avgil-Tsadok, Meytal; Jackevicius, Cynthia; Essebag, Vidal; Eisenberg, Mark J.; Rahme, Elham; Behlouli, Hassan; Pilote, Louise (Thrombosis and Haemostasis, 2016)
In elderly patients (≥75 years), evidence of dabigatran efficacy is lacking and increased vigilance is warranted. We aimed to assess dabigatran effectiveness and safety in elderly patients in real-world practice. We conducted a population-based study using administrative databases, in Quebec (1999–2013). Dabigatran users (110/150 mg) were compared with matched warfarin users with regard to stroke and bleeding events. Age was categorised into < 75 or ≥ 75 years. Propensity score adjusted models were used. The cohort consisted of 15,918 dabigatran users and 47,192 matched warfarin users, with 67.3 % being elderly patients. The elderly predominantly used the lower dose (80.1 %) while younger patients mainly used the higher dose (80.0 %). In multivariable analyses adjusted for propensity score, the risk of stroke in elderly patients using dabigatran, was no different than the risk in warfarin users (HR 1.05, 95 % CI: 0.93, 1.19) regardless of dabigatran dose. However, dabigatran was associated with lower rates of intracranial haemorrhage (HR 0.60, 95 % CI: 0.47–0.76) and higher rates of gastrointestinal bleeding (HR 1.30 95 % CI: 1.14–1.50) when compared to warfarin. Based on real-life experience, dabigatran can offer an alternative to warfarin in elderly patients, with fewer intracranial bleeding events. However, caution is warranted for gastrointestinal bleeding.
Keywords: Anticoagulants; atrial fibrillation; bleeding; elderly; stroke